1996
DOI: 10.1523/jneurosci.16-21-06864.1996
|View full text |Cite
|
Sign up to set email alerts
|

Selective Innervation of Fast and Slow Muscle Regions during Early Chick Neuromuscular Development

Abstract: The electrical properties of adult motoneurons are well matched to the contractile properties of the fast or slow muscle fibers that they innervate. How this precise matching occurs developmentally is not known. To investigate whether motoneurons exhibit selectivity in innervating discrete muscle regions, containing either fast or slow muscle fibers during early neuromuscular development, we caused embryonic chick hindlimb muscles to become innervated by segmentally inappropriate motoneurons. We used the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 52 publications
(85 reference statements)
4
32
0
Order By: Relevance
“…Accordingly, chick muscles with predominant fast or slow myosin composition were detectable in vivo even when neuromuscular transmission was completely blocked by curare since early embryonic stages (171). In chick embryos, nerve-independent diversification of muscle fibers occurs concomitantly with muscle-independent diversification of motor neuron, supporting the hypothesis that different classes of motoneurons innervate selectively muscle fibers of the appropriate type during early neuromuscular development (633).…”
Section: A Fiber Types In Trunk and Limb Muscle During Embryonic Devmentioning
confidence: 66%
“…Accordingly, chick muscles with predominant fast or slow myosin composition were detectable in vivo even when neuromuscular transmission was completely blocked by curare since early embryonic stages (171). In chick embryos, nerve-independent diversification of muscle fibers occurs concomitantly with muscle-independent diversification of motor neuron, supporting the hypothesis that different classes of motoneurons innervate selectively muscle fibers of the appropriate type during early neuromuscular development (633).…”
Section: A Fiber Types In Trunk and Limb Muscle During Embryonic Devmentioning
confidence: 66%
“…Such recordings are able to detect the firing of individual motor units. Extensive past studies (Landmesser and O'Donovan, 1984a,b;Rafuse et al, 1996) have demonstrated the highly stereotyped bursting patterns of each motoneuron pool and the maintenance of these patterns when motoneurons are forced to innervate foreign muscles (Landmesser and O'Donovan, 1984b;Rafuse et al, 1996). Similar recordings were also made from the novel nerves that innervated the sartorius muscle in the sarcosine recovery embryos.…”
Section: Methodsmentioning
confidence: 81%
“…5A, top trace, black bar), the sartorius usually exhibits a prolonged burst (top trace, asterisk) that often lasts until the next femorotibialis burst, whereas the femorotibialis is silent during this period (bottom trace, arrowhead) (n ϭ 9 for control recordings). Previous studies have shown that when embryonic chick motoneurons were surgically forced to innervate foreign muscles, they maintained their original pool-specific bursting patterns (Landmesser and O'Donovan, 1984b;Rafuse et al, 1996), which result from a combination of intrinsic membrane properties and central connectivity. Thus, if motoneurons did not have their identities altered in the sarcosine-treated embryos but simply projected to the wrong muscle, one would expect to see, when recording from the sartorius, that femorotibialis motoneurons would burst during the sartorius inhibitory period.…”
Section: Motoneurons That Innervate Foreign Muscles In Sarcosinetreatmentioning
confidence: 99%
“…The present study followed chicken spinal motor axons from the initial segment to the internodes by TEM of serial sections in order to determine whether there is a sudden morphological change between the unmyelinated and myelinated part. The chicken neuromuscular system has several advantages for muscle-nerve studies (Rafuse et al 1996). For example, fast and slow primary myotubes are segregated into distinct fast and slow regions that are distributed in a characteristic spatial pattern (McLennan, 1983) so that the innervating motoneurons can be easily labelled by injecting horseradish peroxidase (HRP).…”
Section: Introductionmentioning
confidence: 99%